Increased Nurses' Understanding of Nursing Documentation Based Electronic Health Record (EHR) Through Training - Zakiyah, Ana (Kirana Publisher (KNPub), 2024)
Understanding nurses in the nursing documentation system influences nursing behaviour in documenting nursing care. Innovation and awareness of the importance of using technology can also improve the quality of nursing care. Electronic Health Record (EHR) facilitates nurses to improve work efficiency and generate more time to improve the quality of care services. In addition, aims to maintain the security and confidentiality of patient data. This study aimed to determine nurses' understanding before and after being given training on nursing documentation and EHR. The research design used pre-experimental. The sample of this study was the head of the room and the team leader, totalling 45 respondents. This activity integrates several methods, including lectures, brainstorming, and case simulations in documenting nursing care. Nurses' comprehension was measured before and after training using questionnaires. The process of data analysis using the Wilcoxon signed rank test obtained p-value of 0.000 < 0.005. Nurses' understanding has improved compared to before the training. Continuous training on and monitoring evaluation of documentation accuracy will improve the quality of nursing care documentation.